2022
DOI: 10.1021/acsomega.1c04989
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Differences in Prion Protein Conformation by Quantifying Methionine Oxidation

Abstract: A prion's pathogenic character is enciphered in its conformation, which also defines the chemical environments of its amino acids. Differences in chemical environments influence the reactivity of amino acid side chains, in a conformation-dependent manner. Chemical oxidation of susceptible methionines would identify those methionines on the surface of a prion, which would reveal conformation-dependent information. We identified a set of methionine-containing peptides derived from the tryptic, chymotryptic, or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…However, after 15 min of chymotryptic digestion, an observed difference (p < 0.04) between the extent of oxidation of the methionines in the peptide was seen, indicating that chymotrypsin preferentially cleaves the unoxidized methionine. 41 Cervids possess a polymorphism at position 132, where the methionine is replaced by leucine. The peptide, LLGSAMSR, is produced by the tryptic digestion of elk PrP.…”
Section: Inmentioning
confidence: 99%
See 3 more Smart Citations
“…However, after 15 min of chymotryptic digestion, an observed difference (p < 0.04) between the extent of oxidation of the methionines in the peptide was seen, indicating that chymotrypsin preferentially cleaves the unoxidized methionine. 41 Cervids possess a polymorphism at position 132, where the methionine is replaced by leucine. The peptide, LLGSAMSR, is produced by the tryptic digestion of elk PrP.…”
Section: Inmentioning
confidence: 99%
“…We have observed that chymotrypsin preferentially cleaves at the carboxyl terminus of methionine over that of the sulfoxide analogue. 41 Thus, an extended chymotrypsin digestion can skew the proportion of oxidized methionine in a sample.…”
Section: Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Several of these are modifications known to occur during sample processing (e.g., oxidation) or electrospray ionisation MS (e.g., water loss, ammonia loss and metal adducts) [32]. However, although oxidation is sometimes associated with sampling processing, it is impossible to rule out that some sites that have been reported previously may have a biological significance [6,23,33]. For this reason, this modification has been included in our analysis.…”
Section: Identification Of Ptms By Msmentioning
confidence: 99%